Defect-assisted reversible phase transition in mono- and few-layer ReS2 - George Zograf; Andrew B. Yankovich; Betül Küçüköz; Abhay V. Agrawal; Alexander Yu. Polyakov; Joachim Ciers; Fredrik Eriksson; Åsa Haglund; Paul Erhart; Tomasz J. Antosiewicz; Eva Olsson; Timur O. Shegai (npj 2D Materials and Applications, 2025)
Abstract 2D transition metal dichalcogenide (TMD) materials have attracted interest due to their remarkable excitonic, optical, electrical, and mechanical properties, which are dependent on their crystal structure. Consequently, controlling the crystal structure of these materials is essential for fine-tuning their performance, e.g., linear and nonlinear optical, as well as charge transport properties. While various phase-switching TMD materials are available, their transitions are often irreversible. Here, we investigate the mechanism of a light-induced reversible phase transition in mono- and bilayer rhenium disulfide (ReS2). Our observations, based on transmission electron microscopy, nonlinear spectroscopy, and density functional theory, reveal a transition from the ground $${\rm{T}}^{′′}$$ T ″ (double-distorted T) to the metastable $${\rm{H}}^{′}$$ H ′ (distorted H) phase under femtosecond laser irradiation or influence of highly-energetic electrons. We show that the formation of sulfur vacancies facilitates this phenomenon. Our findings pave the way toward manipulating the crystal structure of ReS2 and possibly its heterostructures.